(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Alzheimer’s disease is a progressive neurodegenerative disorder characterized by cognitive decline, memory impairment and neuronal loss. The complex and multifactorial nature of Alzheimer’s disease limits the effectiveness of conventional single target therapies and necessitates the development of novel therapeutic agents capable of modulating multiple disease associated targets simultaneously. In the present study, a series of ten novel triazole substituted carbazole derivatives were rationally designed and evaluated as potential multifunctional anti-Alzheimer’s agents using an in silico drug discovery approach. The chemical structures were constructed using ACD Lab ChemSketch and subsequently assessed for their physicochemical properties, drug likeness, pharmacokinetic behaviour and toxicity profiles through Swiss ADME, admetSAR and PASS Online. Compounds exhibiting favourable ADMET properties and compliance with Lipinski’s rule of five were selected for further analysis. Molecular docking studies were performed using Auto Dock Vina against two validated therapeutic targets involved in the Alzheimer’s disease pathogenesis, acetylcholinesterase (AChE) and β-secretase-1 (BACE-1) to evaluate their binding affinity and inhibitory potential. Several designed derivatives demonstrated strong binding affinities towards both targets and established stable interactions with key active site amino acid residues through hydrogen bonding, hydrophobic contacts and π-π interactions and they are confirmed by protein-ligand interaction analysis using BIOVIA Discovery Studio. These findings suggest that the designed triazole-substituted carbazole derivatives could serve as promising lead molecules for anti-Alzheimer’s activity and may be considered for future synthesis and experimental evaluation.